A simplicity criterion for symmetric operator on a graph - Kandagura, A. N.; Ashurova, E. N.; Karpenko, I. I. (Methods of Functional Analysis and Topology, 2014)
In the present paper we show that the topology of the underlying graph determines the domain and deficiency indices of a certain associated minimal symmetric operator. We obtaine a criterion of simplicity for the minimal operator associated with the graph.